EZH2 Regulates Lipopolysaccharide-Induced Periodontal Ligament Stem Cell Proliferation and Osteogenesis through TLR4/MyD88/NF-κB Pathway - Pengcheng Wang; Huan Tian; Zheng Zhang; Zuomin Wang (Hindawi Limited, 2021)
Background. Periodontitis induced by bacteria especially Gram-negative bacteria is the most prevalent chronic inflammatory disease worldwide. Emerging evidence supported that EZH2 plays a significant role in the inflammatory response of periodontal tissues. However, little information is available regarding the underlying mechanism of EZH2 in periodontitis. This study is aimed at determining the potential role and underlying mechanism of EZH2 in periodontitis. Methods. The protein levels of EZH2, H3K27ME, p-p65, p-IKB, TLR4, MyD88, Runx2, and OCN were examined by western blot assay. Proliferation was evaluated by CCK8 assay. The levels of TNFα, IL1β, and IL6 were detected by ELISA assay. Migration was detected by wound healing assay. The distribution of p65 was detected by immunofluorescence. The formation of mineralized nodules was analyzed using alizarin red staining. Results. LPS stimulation significantly promoted EZH2 and H3K27me3 expression in primary human periodontal ligament stem cells (PDLSCs). Targeting EZH2 prevented LPS-induced upregulation of the inflammatory cytokines and inhibition of cell proliferation and migration. Furthermore, EZH2 knockdown attenuated the TLR4/MyD88/NF-κB signaling to facilitate PDLSC osteogenesis. Conclusions. Modulation of the NF-κB pathway through the inhibition of EZH2 may offer a new perspective on the treatment of chronic apical periodontitis.